2021
DOI: 10.3390/polym13111694
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Property of Polypropylene Composites and Functionalized Copper Nanoparticles

Abstract: Copper nanoparticles (CuNPs) functionalized with polyethyleneimine (PEI) and 4-aminobutyric acid (GABA) were used to obtain composites with isotactic polypropylene (iPP). The iPP/CuNPs composites were prepared at copper concentrations of 0.25–5.0 wt % by melt mixing, no evidence of oxidation of the CuNP was observed. Furthermore, the release of copper ions from iPP/CuNPs composites in an aqueous medium was studied. The release of cupric ions was higher in the composites with 2.5 and 5.0 wt %. These composites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…The last results agree with the studies reported by Jardón-Maximino et al concerning CuNPs coated with nitrogen-based ligands, finding that this type of ligand prevents the oxidation of CuNPs under atmospheric conditions over 60 months [37]. Later, the same authors found that protection of CuNPs occurs even at more drastic conditions such as in the elaboration of nanocomposites by melt processing [38].…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 90%
See 1 more Smart Citation
“…The last results agree with the studies reported by Jardón-Maximino et al concerning CuNPs coated with nitrogen-based ligands, finding that this type of ligand prevents the oxidation of CuNPs under atmospheric conditions over 60 months [37]. Later, the same authors found that protection of CuNPs occurs even at more drastic conditions such as in the elaboration of nanocomposites by melt processing [38].…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 90%
“…Polymers 2021, 13, x FOR PEER REVIEW 9 of 12 at more drastic conditions such as in the elaboration of nanocomposites by melt processing [38].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…This behavior suggests a strong interaction between the copper and the polar groups of the stabilizers. Such interaction could be an advantage in producing polymeric nanocomposites [ 35 ], but could also have negative effects on other applications, such as electrically conductive materials, where it is desirable to remove the coating from Cu NPs at low temperatures [ 17 ]. At 600 °C, complete thermal degradation of the organic material and weight gain as a result of oxidation of the metallic copper was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas aeruginosa (ATCC 13388) Gram-negative and Staphylococcus aureus (ATCC 6538) Gram-Positive were used for the tests, they were purchased from American Type Culture Collection (Manassas, VA, USA). The procedure to evaluate the antibacterial activity was recently reported by our research group [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cu ions sterilization properties are due to the generation of hydroxyl radicals that oxidize bacterial proteins, lipids, DNA, and other (macro)molecules [ 117 ]. Noteworthy, numerous reports about copper nanoparticles for antimicrobial applications have been published recently [ 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ]. The POSS particles can also be used as an immobilization agent for copper nanoparticles (Cu-NP).…”
Section: Biomedical Applications Of Pu/possmentioning
confidence: 99%